Micro-Mobility Enhancement in Multicast Mobile Ipv6 Wireless Networks - Yong, Chu Eu (2006)
Mobile Internet Protocol version 6 (MIPv6) has been proposed to solve the problem of mobility in the new era of Internet. Mobile IPv6 allows mobile devices always addressable by its home address wherever it is located. Previous research has shown that MIPv6 only defines a means of managing global mobility (macro-mobility) but does not address local mobility (micro-mobility) separately. Instead, it uses the same mechanism in both cases. This involves long handover delay and a lot of signaling.